Biopsychosocial approach in vasculitis: BETY - Barlak, Aysima; Ünal, Edibe (Acta Medica, 2025)
Rheumatic diseases cause biopsychosocial effects such as chronic pain, fatigue, social isolation, functional impairments, anxiety-depression, and sleep problems. National and international guidelines emphasize the importance of physical activity and exercise planning, patient education and self-management skills, and psychosocial interventions in the management of rheumatic diseases. Vasculitides are also a group of chronic diseases that can affect many organs and systems, impacting individuals biopsychosocially. Although comprehensive approaches are recommended in the literature for this disease group, as in other rheumatic diseases, studies in this field are quite insufficient. The Cognitive Exercise Therapy Approach (Bilişsel Egzersiz Terapi Yaklaşımı - BETY) is an innovative exercise approach developed on the basis of the biopsychosocial model for individuals diagnosed with rheumatological diseases. Developed based on the biopsychosocial model, the BETY exercise model is an example of a non-pharmacological exercise approach in the treatment of vasculitis.